2020
DOI: 10.1038/s41467-020-18133-0
|View full text |Cite
|
Sign up to set email alerts
|

Feeding-dependent tentacle development in the sea anemone Nematostella vectensis

Abstract: In cnidarians, axial patterning is not restricted to embryogenesis but continues throughout a prolonged life history filled with unpredictable environmental changes. How this developmental capacity copes with fluctuations of food availability and whether it recapitulates embryonic mechanisms remain poorly understood. Here we utilize the tentacles of the sea anemone Nematostella vectensis as an experimental paradigm for developmental patterning across distinct life history stages. By analyzing over 1000 growing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 55 publications
(72 reference statements)
0
27
0
Order By: Relevance
“…These observed differences between Sym and Apo lacerates could also be explained by a lack of nutrients in general in Apo lacerates, not necessarily those specifically derived from symbionts. In the non-symbiotic anemone Nematostella vectensis , new tentacle growth in primary polyps is supported by localized nutrient-dependent cell proliferation ( Ikmi et al, 2020 ). In the absence of food sources ( i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observed differences between Sym and Apo lacerates could also be explained by a lack of nutrients in general in Apo lacerates, not necessarily those specifically derived from symbionts. In the non-symbiotic anemone Nematostella vectensis , new tentacle growth in primary polyps is supported by localized nutrient-dependent cell proliferation ( Ikmi et al, 2020 ). In the absence of food sources ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these previous descriptions of pedal laceration, the process of how tentacles and mesenteries are patterned throughout development is unknown. Several studies in the non-symbiotic anemone Nematostella vectensis have characterized both tentacle and mesentery patterning during different stages of postembryonic development ( Genikhovich et al, 2015 ; He et al, 2018 ; Ikmi et al, 2020 ). During metamorphosis from larvae to primary polyp, Nematostella mesenteries are the first structures to develop followed by the four primary tentacles ( Genikhovich et al, 2015 ; He et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, it will be uttermost interesting to determine if and how TOR is involved in these adaptive growth patterns, and genetic screens will be invaluable tools to gain further knowledge. Interestingly, a very recent report showed that the sea anemone Nematostella vectensis also produces new tentacles throughout its life cycle in a nutrient-regulated manner and under the control of TOR [108]. This could suggest a convergent evolution during the independent acquisition of multicellularity by plants and early animals, which rewired the primordial TOR signaling pathway to promote organ inception in a nutrient-driven manner.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…1 a). Interestingly, in cnidarians, there are some lineages that show bilateral symmetry [ 1 , 4 , 5 , 9 11 ] (Fig. 1 a).…”
Section: Introductionmentioning
confidence: 99%